2012
DOI: 10.2196/jmir.2202
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Research on the Internet: Medical Record Data Integration with Patient-Reported Outcomes

Abstract: BackgroundThe growth in the number of patients seeking health information online has given rise to new direct-to-patient research methods, including direct patient recruitment and study conduct without use of physician sites. While such patient-centric designs offer time and cost efficiencies, the absence of physician-reported data is a key concern, with potential impact on both scientific rigor and operational feasibility.ObjectiveTo (1) gain insight into the viability of collecting patient-reported outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The introduction of Internet-based information technology (IT) into the health care system is widely perceived as a significant step to improve the quality of services provided by health care institutions [ 1 - 5 ]. As a result, transition of paper medical records to electronic ones is becoming more common in health care systems around the globe [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of Internet-based information technology (IT) into the health care system is widely perceived as a significant step to improve the quality of services provided by health care institutions [ 1 - 5 ]. As a result, transition of paper medical records to electronic ones is becoming more common in health care systems around the globe [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns over patient privacy and the need for computer literacy, which may affect generalisability of any research findings . Study retention is considered to be higher where there is direct patient interaction because of the explicit alignment of patient incentives; the patient learns about the study directly, understands what is required, self‐consents to participate, and then self‐reports study information . Jamison et al found better rates of compliance with electronic patient reported outcomes (PROs) than paper based PROs.…”
Section: Resultsmentioning
confidence: 99%
“…When expanding the linkage methodology to include databases such as electronic medical records [ 26 ], it is important to take the privacy aspect into account. It has been strongly argued that important privacy concerns must be interpreted alongside the social good that can come from this kind of health research [ 27 - 30 ].…”
Section: Discussionmentioning
confidence: 99%